Eurocentrism in European history and memory - Brolsma, Marjet 1978- Herausgeber; Bruin, Robin de, 1971- 1971- Herausgeber; Lok, Matthijs, 1974- 1974- Herausgeber (Amsterdam University Press, 2019)
Eurocentrism means seeing the world in Europe's terms and through European eyes; while this may not seem so unreasonable to Europeans, this perspective has unforeseen consequences. Eurocentric history implies that scientific modernity has diffused outwards from Europe to the benefit of the rest of the world, through colonialism and later development aid; it involves the imposition of European norms on places and times where they are often quite inappropriate. This book brings together respected scholars from history, literature, art, memory and cultural policy, and from different geographical perspectives, who explore and critically analyse manifestations of Eurocentrism in representations of Europe's past. The collection investigates the role imaginings of the European past since the 18th Century played in the construction of a Europeanist world view and the ways in which 'Europe' was constructed in literature and art